Exercise and physical activity in asylum seekers in Northern England; using the theoretical domains framework to identify barriers and facilitators - Melanie Haith-Cooper; Catherine Waskett; Jane Montague; Maria Horne (BMC, 2018)
Abstract Background Many asylum seekers have complex mental health needs which can be exacerbated by the challenging circumstances in which they live and difficulties accessing health services. Regular moderate physical activity can improve mental health and would be a useful strategy to achieve this. Evidence suggests there are barriers to engaging black and minority ethnic groups in physical activity, but there is little research around asylum seekers to address the key barriers and facilitators in this group. Methods A two stage qualitative study used semi-structured interviews underpinned by the Theoretical Domains Framework. The interviews were conducted in voluntary sector groups in four towns/ cities in Northern England. Purposive sampling recruited 36 asylum seekers from 18 different countries. Interviews were audio recorded, transcribed verbatim and subject to framework analysis. Stage two involved a nominal group technique with five key stakeholders including asylum seekers and those that work with them. They followed a four stage process to rank and reach consensus on the key barrier to undertaking physical activity/ exercise that could be addressed locally through a future intervention. Results A number of barriers and facilitators were identified including a lack of understanding of the term physical activity and recommended levels but knowledge of the health benefits of physical activity/ exercise and the motivation to increase levels having engaged with activities back home. Living as an asylum seeker was considered a barrier due to the stress, poverty and temporary nature of living in an unfamiliar place. The outcome of the nominal group technique was that a lack of knowledge of facilities in the local area was the prevailing barrier that could be addressed. Conclusions Public health practitioners could develop interventions which capitalise on the motivation and knowledge of asylum seekers to encourage an increase in physical activity which may in turn reduce the breadth and depth of mental health needs of this group.